Hubungan Antara Akne Vulgaris Dengan Tingkat Kualitas Hidup Pada Remaja Di Sma Muhammadiyah 2 Surakarta - Ningrum, Pratiwi Fatmasari, dr. Ratih Pramuningtyas, Sp.KK (2016)
Background: Acne vulgaris (AV) is a disease affecting the pilosebaceous unit that mainly occurs in adolescents and is characterized by the formation of comedones, papules, pustules, which can be cured by itself. Acne vulgaris is known to have an impact on the quality of life of sufferers, especially in people who are concerned with appearance.Objective: This research aimed is to determine the relation between acne vulgaris with the level of quality of life in adolescents at SMA Muhammadiyah 2 Surakarta.Methods: This research used observational method with cross sectional approach, using simple random sampling technique, with a sample of 64 respondents. The data obtained through physical examination diagnosed with GAGS by general practitioners and questionnaires from CADI were then analyzed using the chi-square.Results: On the positive acne obtained 40.9% of adolescents have aquality of life. CADI scores in dicateimpaired quality of life of patients AV from mild, moderate to severe. Based on Chi-square test results to determine the relation between acne vulgaris with the level of quality of life in adolescents p value= 0.000 (p <0.005), so it can be concluded that thereis a significant relation between acne vulgaris with the level of quality of life.Conclusion: There is a relation between acne vulgaris with the level of quality of life in adolescents.